PROPUESTA DE MEJORAMIENTO DE INDICADORES DE SERVICIO Y GESTION PARA LA EMPRESA KENTUCKY FRIED CHICKEN KFC-BARRANQUILLA (2013)
This paper presents an improvement plan for the company KFC Barranquilla, located in the Mall Buena Vista. It consists of two related projects that seek to provide an improved service system and enterprise management. The first is an analysis of the waiting line by queuing theory. It begins by calculating the performance parameters through the M/M/1 queuing model, and subsequently develops the model M / M / S. Once the analyzes based on the characterization of the arrival of guests, length of service and the definition of the performance parameters, we propose an improvement plan that defines an optimal number of servers, whose main component is the value of performance parameter average waiting time in queue. This would improve the level of customer satisfaction in accordance with the quality policy timeout of the company and customer. In the second, a diagnosis is made the management system of the company through a survey of workers containing criteria Colombian Award for Quality Management. Based on the results of the survey is designed improvement plan that identifies the strengths and weaknesses of the quality of the company, the latter are proposed as improvement opportunities that will serve the company to improve aspects such as: Personal internal processes, work methods, tools and meeting strategic interest groups associated.